INDEPENDENT LEARNING AS A FACTOR OF PERSONAL DEVELOPMENT - Ergashova Feruza Yuldashevna (Modern American Journals, 2026)
Independent learning has become a central concept in modern education, reflecting the shift from teacher-centered instruction to learner-centered paradigms. This article explores independent learning as a crucial factor in personal development, examining its theoretical foundations, methodological implications, and practical outcomes. The study analyzes contemporary research in pedagogy, psychology, and educational technology to determine how autonomous learning fosters cognitive growth, critical thinking, self-regulation, and lifelong learning skills. A mixed-method research design is proposed to assess the impact of independent learning strategies on students’ personal and academic development. The findings suggest that structured independent learning environments significantly enhance learners’ motivation, responsibility, and adaptability, thereby contributing to holistic personal growth. The study concludes that independent learning is not merely an instructional strategy but a transformative educational paradigm that enhances personal agency and adaptability in a rapidly changing world.
Keywords: Independent learning, personal development, learner autonomy, self-regulated learning, lifelong learning, metacognition, educational methodology.